Strategic Synthesis of ‘Picket Fence’ Porphyrins Based on Nonplanar Macrocycles - Norvaiša, Karolis (John Wiley and Sons Inc., 2021)

(untitled) (European J Org Chem)
Traditional ‘picket fence’ porphyrin systems have been a topic of interest for their capacity to direct steric shielding effects selectively to one side of the macrocycle. Sterically overcrowded porphyrin systems that adopt macrocycle deformations have recently drawn attention for their applications in organocatalysis and sensing. Here we explore the combined benefits of nonplanar porphyrins and the old molecular design to bring new concepts to the playing field. The challenging ortho‐positions of meso‐phenyl residues in dodecasubstituted porphyrin systems led us to transition to less hindered para‐ and meta‐sites and develop selective demethylation based on the steric interplay. Isolation of the symmetrical target compound [2,3,7,8,12,13,17,18‐octaethyl‐5,10,15,20‐tetrakis(3,5‐dipivaloyloxyphenyl)porphyrin] was investigated under two synthetic pathways. The obtained insight was used to isolate unsymmetrical [2,3,7,8,12,13,17,18‐octaethyl‐5,10,15,20‐tetrakis(2‐nitro‐5‐pivaloyloxyphenyl)porphyrin]. Upon separation of the atropisomers, a detailed single‐crystal X‐ray crystallographic analysis highlighted intrinsic intermolecular interactions. The nonplanarity of these systems in combination with ‘picket fence’ motifs provides an important feature in the design of supramolecular ensembles.